PENDAMPINGAN PENDAYAGUNAAN INFORMASI BERBASIS DIGITAL UNTUK PENGEMBANGAN KARAKTER POSITIF SISWA SMK PP NEGERI JAMBI - K.A. Rahman; Mohammad Muspawi; Robin Pratama (Universitas 45 Surabaya, 2022)
This community service aims to provide assistance for students in utilizing digital-based information so that they can provide positive directions for character building. The method consists of both small and large lectures then simulations, individual and classical approaches. In this mentoring all participants will work well individually or in groups. The lecture method will be used to provide direction to participants regarding matters related to digital literacy and positive character for students so they can have strong motivation and have positive character as they should. Utilization of Information and Communication Technology (ICT) continues to make a significant contribution to the development of students at SMK PP Negeri Jambi, to become human beings with character and intellectual intelligence. It is necessary to apply the following principles: The use of ICT in education should take into account the characteristics of students, educators and educational staff in the overall decision to make ICT; The use of ICT should be designed to strengthen the user's interest and motivation to improve themselves intellectually, spiritually, socially, and physically; Utilization of ICT should encourage users to be more creative and innovative so that they are not only satisfied with being consumers of ICT-based information.